Applications and challenges of porous carbon with different dimensions in supercapacitors—a mini review - Liu, Yong; Chen, Hongyu; Li, Liqing (Frontiers in Energy Research, 2022)
The rapid development of modern electronic technology is in urgent need of further breakthroughs to actualize high-energy, high-power, and long cycling energy storage equipment. Carbon-based supercapacitors (CSs) are potential high-power devices that can stock electrical energy at the electrode–electrolyte interface rather than by diffusing ions inside electrodes. However, the commercial CSs using active carbon (AC) suffer from restricted energy densities on account of relatively small specific surface area, poor porosity, and low electrochemical activity. In recent years, various tactics have been applied to enhance the electrochemical properties of carbon-based electrode, and fruitful successes have been achieved. This mini review first introduces the concerned charge storage mechanisms of CSs, which is followed by a straightforward summary of the pivotal factors affecting the electrochemical performance. Then, the novel fabrication strategies of porous carbon at different dimensions are exemplified and summarized to prepare large-capacitance electrodes. The current challenges and promising future research for exploiting the state-of-the-art supercapacitors are also discussed.